Seroepidemiology of Toxoplasma Gondii in kidney transplant patients - Marzieh Latifi; Habib Rahban; Elahe Pourhosein; Tannaz Hajialireza Tehrani; Parisa Mahjoobi; Sanaz Dehghani (Caspian Journal of Internal Medicine)
Background: Opportunistic infection after transplantation is a serious problem, with Toxoplasma Gondii (T.gondii) and cytomegalovirus being the most concerning infections. The objective of this research was to examine the seroepidemiology of the T. gondii virus among kidney transplant recipients at Sina Hospital in Tehran from 2017 to 2021. Methods: A total of 342 kidney transplant patients participated in this cross-sectional study using the census method after obtaining consent. Data were collected by reviewing medical records and the transplant database, including demographic characteristics and infectious tests related to kidney transplantation. The collected information was entered into SPSS18 software. Results: The age of the subjects ranged from 10 to 73 years, with 125 patients having kidney failure due to ERDS. The rate of exposure to T. gondii in kidney transplant patients was 54.2%. 125 patients experiencing kidney failure due to ERDS. In kidney transplant patients, the exposure rate to T. gondii was 54.2%. There is a positive correlation between TOX IgG and age (r= 0.12, P = 0.02). There is a positive correlation between CMV IgG and the time elapsed since kidney transplantation (r = 0.11, P = 0.03) and TOX IgG (r = 0.13, p < 0.01). Gender was found not to predict EBV.IgG (β = 0.787, p < 0.21), CMV.IgG (β = 4.752, p < 0.071), TOX.IgG (β = 1.154, p < 0.256) based on regression tests. Conclusion: Physicians should be aware of preventive measures and should consider early diagnosis in cases of compatible symptoms. Screening for anti-Toxoplasma IgM antibodies in potential donors is recommended.